2022
DOI: 10.1021/acssuschemeng.2c02919
|View full text |Cite
|
Sign up to set email alerts
|

Cu–S Bonds as an Atomic-Level Transfer Channel to Achieve Photocatalytic CO2 Reduction to CO on Cu-Substituted ZnIn2S4

Abstract: Due to the intrinsic chemically inert CO 2 with the dissociation energy of C�O bond as high as 750 kJ mol −1 , low efficiency and selectivity have become the most significant restraints for the practical application of photocatalytic CO 2 reduction. Renewing the electronic structure of adsorbed CO 2 on the catalyst surface through a rational catalyst design is crucial to achieving performance improvement. Herein, we prepared ZnIn 2 S 4 and Cu-substituted ZnIn 2 S 4 containing both Lewis acid and Lewis base sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…4 inset). 32,33 It should be noted that the selective photocatalytic CO 2 to CO conversion performance of Cu@Co 24 is comparable to that of MAF-34-CoRu 40 and superior to that of some of the Cu-based or Co-based catalysts (Table S3, ESI †).…”
Section: àmentioning
confidence: 95%
See 1 more Smart Citation
“…4 inset). 32,33 It should be noted that the selective photocatalytic CO 2 to CO conversion performance of Cu@Co 24 is comparable to that of MAF-34-CoRu 40 and superior to that of some of the Cu-based or Co-based catalysts (Table S3, ESI †).…”
Section: àmentioning
confidence: 95%
“…Given the optical properties of Cu@Co 24 and the CO 2activation nature of Cu-based species, [32][33][34][35] the CO 2 photoreduction experiments of Cu@Co 24 were explored. Photocatalysis was performed by introducing a gas mixture of CO 2 and H 2 O into a sealed reaction system containing the as-synthesized catalysts.…”
mentioning
confidence: 99%
“…Compared to CH 4 , efficient CO 2 conversion in dry reforming of a methane reaction at low temperatures is more difficult due to the higher bond energy of CO in CO 2 (750 kJ·mol –1 ) than C–H in CH 4 (434 kJ·mol –1 ). , Remarkable efforts have been made to improve the activation of CO 2 at low temperatures, such as increasing alkaline sites and/or oxygen vacancies. , The latter is found to promote the adsorption and activation of CO 2 accordingly, improving the stability of the catalyst. , Safavinia et al found that the high dispersion of Ni 2+ ions in the core of CeO 2 –ZrO 2 nanoparticles could enhance the concentration of oxygen vacancies, thereby enhancing the catalytic performance of the catalyst for methane dry reforming . In addition, the oxygen vacancy could enhance the exchange of surface oxygen species and lattice oxygen species .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to CH 4 , efficient CO 2 conversion in dry reforming of a methane reaction at low temperatures is more difficult due to the higher bond energy of C�O in CO 2 (750 kJ•mol −1 ) than C−H in CH 4 (434 kJ•mol −1 ). 14,15 Remarkable efforts have been made to improve the activation of CO 2 at low temperatures, such as increasing alkaline sites and/or oxygen vacancies. 2,16 The latter is found to promote the adsorption and activation of CO 2 accordingly, improving the stability of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] However, the photocatalytic efficiency remains unsatisfactory because the stubborn C]O double bond in a nonpolar CO 2 molecule requires high energy for activation, leading to sluggish kinetics issues. [11][12][13] In light of this, great efforts have been devoted to optimizing the structure of photocatalysts so as to improve the conversion and selectivity of CO 2 reduction. [14][15][16][17] Up to now, a variety of photocatalysts with tailorable band structures have been explored, especially semiconductors (such as TiO 2 , Zn 2 CeO 4 , and C 3 N 4 ).…”
Section: Introductionmentioning
confidence: 99%